2020
DOI: 10.2174/1381612826666200707132920
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Chloroquine and Hydroxychloroquine in Immune Regulation and Diseases

Abstract: : Chloroquine (CQ) and hydroxychloroquine (HCQ) are derivatives of the heterocyclic aromatic compound quinoline. These economical compounds were used as antimalarial agents for many years. Currently, they are used as monotherapy or in conjunction with other therapies for the treatment of autoimmune diseases such as systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), Sjögren's syndrome (SS) and antiphospholipid antibody syndrome (APS). Based on its effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 247 publications
0
33
0
Order By: Relevance
“…11,12 HCQ has many other mechanisms including change in lysosomal pH leading to reduced TLR signalling, decrease in pro-inflammatory cytokine release, induction of apoptosis, and inhibition of autophagy. 14 However, the clinical studies are conflicting in terms of the protective role of HCQ in the prevention of COVID-19. It has been shown that after high-risk or moderate-risk exposure to COVID-19, HCQ did not prevent illness when used as post-exposure prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 HCQ has many other mechanisms including change in lysosomal pH leading to reduced TLR signalling, decrease in pro-inflammatory cytokine release, induction of apoptosis, and inhibition of autophagy. 14 However, the clinical studies are conflicting in terms of the protective role of HCQ in the prevention of COVID-19. It has been shown that after high-risk or moderate-risk exposure to COVID-19, HCQ did not prevent illness when used as post-exposure prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…13 So, hydroxychloroquine has both direct anti-viral effects and anti-inflammatory effects. 14 Various multi-centric clinical trials are being conducted to study the effect of this drug on prophylaxis as well as treatment of COVID-19. However, the evidence at present is not definitive regarding the role of HCQ.…”
Section: Introductionmentioning
confidence: 99%
“…HCQ, as an aminoquinoline, has been extensively used for the prevention and therapy of malaria and rheumatic diseases (Martinez et al 2020). In the context of the COVID-19 pandemic and absence of effective drugs, HCQ has been approved for the treatment of hospitalized patients with COVID-19 on the grounds of anti-inflammatory and antiviral effects.…”
Section: Discussionmentioning
confidence: 99%
“…All of these drugs would impair primary T cell responses but may not block recall responses. Induction of CD4 + T cells could be inhibited by preventing antigen presentation through the MHC class II pathway through chloroquine, which prevents acidification of endosomes (118), cyclosporin A and tacrolimus, which both inhibit calcineurin (119) or blockers of the lysosomal protease cathepsin S, such as morpholinurea-leucine-homophenylalaninevinylsulfone-phenyl (120). Some of the drugs such as cyclosporin A and tacrolimus also block MHC class I antigen presentation, which can also be inhibited by proteasome inhibitors such as lactacystin (121) or inhibitors of TAP (122).…”
Section: Cd8 + T Cell Responses To Aav Vectorsmentioning
confidence: 99%